Exploring Nurses’ Perceptions and Challenges in Caring for Resuscitated Patients: Insights into Roles, Attitudes, and Outcomes - Yousef Awadh Alshehri; Abdulaziz Fahad Alharbi; Nouf Nuhaytir Alshammari; Sulaiman Mohammed Al Shamry; Sultan Mohammed Al Shammari; Ahlam AlHulw Alanezi; Norah Alhulw Alanezi; Bushra Suliman Rabee Alahmdi; Jameel Saud Saleh Alsubhi; Haylah Matooq Almalki; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Cardiopulmonary resuscitation (CPR) is a critical life-saving intervention for cardiac arrest patients, with nurses playing a pivotal role in its success. Nurses’ perceptions of resuscitated patients are shaped by their experiences, knowledge, attitudes, and the challenges they encounter during and after resuscitation efforts. This article examines nurses’ perceptions of resuscitated patients, highlighting the emotional, ethical, and organizational factors influencing their attitudes and performance. The role of nurses in CPR is explored, with particular emphasis on their responsibilities as first responders, team members, and post-resuscitation caregivers. Challenges such as emotional distress, resource limitations, and ethical dilemmas are analyzed, alongside factors that shape nurses’ perceptions, including workplace environments, training, and patient outcomes. Strategies for improving nurses’ perceptions and experiences are discussed, including enhancing education, fostering supportive environments, and addressing emotional and ethical barriers. The article underscores the importance of empowering nurses to improve CPR outcomes and outlines future research directions to further understand their perspectives.